(3GdHSjW aj GdJaSjQs - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj GdfjSGHhQj, J (B468 (3g` s
(3ChdgG (B:s
(3Ghdg ef JaSjQ ShQI HQGAI (B: (3ENJdahG ai SHH JQc GdJSejI ai ChdgG s
(3BNQgG (B:s
(3hjfJgi HBNQ ShQI jhSa hBNQ eG ajg (B: (3Gdbhe jDefhf (B: (3Ci jUObhf HeG LGA Hg eMeO Udi Gddg Ydjg hSde s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3JaSjQ (B54) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs